Nonpharmacological intervention module for graded domiciliary care in dementia care at community level: A novel endeavor - Nilanjana Ghosh; Bhaskar Mukherjee; Avik Layek (Wolters Kluwer Medknow Publications, 2021)
Mental health is an oftly neglected topic more so due to stigma associated with the disease. Hence, availability of a user-friendly module can be of immense help to carers improving their mental health, as they often suffer from depression. This in turn may lead to clinical improvement of the patient as well. Integrating each family member into the care practices is also equally important. Nonpharmacological interventions once designed and structured will lead to a standardized care continuum at the community level for all patients and will help as a ready reckoner for the careers to compare their work or call out to each other during times of need. Even the burden on hospitals will decrease which will then mainly focus on patient monitoring pharmacological interventions.